Changes in Antioxidant/Pro-Oxidant Ratio of Brain Tissue Homogenates in Response to Cocos nucifera Treatment - O. N. Ilochi; C. E. Augustine; A. N. Chuemere (Archives of Current Research International, 2022)
Objective: This study revealed the effect of Cocos nucifera juice on antioxidant/pro-oxidant ratio in brain tissue homogenates of wistar rats. Materials and Methods: 40 male wistar rats were collected and randomly selected into 4 groups. Treatment protocols were; i-normal saline, ii-3ml C. nucifera juice, iii-6ml C.nucifera juice, iv-9ml C. nucifera juice. The study period lasted for 42 days. Brain tissue homogenate was prepared and biochemical analysis for antioxidant enzymes superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx); pro-oxidant biomarkers hydrogen peroxide (H2O2), thiobarbituric acid reactive substances (TBARS) and nitric oxide (NO) were assayed for. Results: The result showed that there was an increase in antioxidants concentration and a simultaneous decrease in pro-oxidant species generation as the dose of treatment was increased. The ratio of antioxidants to pro-oxidants showed a direct proportionality to the treatment dose. Conclusion: C. nucifera juice has the ability to improve the level of production or synthesis of the assayed antioxidant enzymes and also has the efficacy to suppress pro-oxidant specie generation.